2011
DOI: 10.1002/jbm.b.31908
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic deposition of bioactive silica‐calcium phosphate nanocomposite on Ti‐6Al‐4V orthopedic implant

Abstract: Bioactive silica-calcium phosphate nanocomposite (SCPC) has been coated on Ti-6Al-4V implant employing an electrophoretic deposition (EPD) technique. The effects of composition and pH of the suspending medium on the zeta potential of three different SCPC formulations; SCPC25, SCPC50 and SCPC75 were analyzed. The average zeta potential of SCPC50 in pure ethanol was more negative than that of SCPC25 or SCPC75; however, the difference was not statistically significant. Discs of Ti-6Al-4V were passivated, coated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…SCPC50 nano-particles were then coated on the Ti-6Al-4V substrates using EPD as previously reported. 21 Ti-6Al-4V samples were passivated in 34% HNO 3 to develop a surface layer of TiO 2 , 23 immersed in a 10 wt % SCPC50 suspension in ethanol, and coated by EPD using a voltage of 50 V for 30 or 60 s. The coated samples were dried in a vacuum dessicator and thermally treated at 800 C for 1 h under argon at a fixed heating and cooling rate of 2 C min 21 . The weight of ceramic deposited on each disc was recorded after sintering.…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…SCPC50 nano-particles were then coated on the Ti-6Al-4V substrates using EPD as previously reported. 21 Ti-6Al-4V samples were passivated in 34% HNO 3 to develop a surface layer of TiO 2 , 23 immersed in a 10 wt % SCPC50 suspension in ethanol, and coated by EPD using a voltage of 50 V for 30 or 60 s. The coated samples were dried in a vacuum dessicator and thermally treated at 800 C for 1 h under argon at a fixed heating and cooling rate of 2 C min 21 . The weight of ceramic deposited on each disc was recorded after sintering.…”
Section: Sample Preparationmentioning
confidence: 99%
“…We have recently reported on the development of bioactive silica-calcium phosphate nanocomposite (SCPC50) coating on Ti-6Al-4V substrate using electrophoretic deposition (EPD). 21 In vitro studies have shown that SCPC50 coating stimulated biological hydroxyapatite formation, enhanced osteoblast differentiation, and induced a low level immunogenic response as compared to the cells attached to uncoated Ti-6Al-4V substrates. 13,21,22 The objective of the present study is to investigate the synergistic effects of surface roughness and material chemistry of SCPC50 coating on modulating key early cellular functions leading to osteoblast differentiation on orthopedic implants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, other animal studies also confirmed the beneficial effects of calcium, such as improved bone formations in rat femora, increased healing of intrabony defects in dog mandibles, and enhanced resistance to dislodgement in rabbit tibia [13][14][15]. Furthermore, silica-calcium phosphate nano-composite coatings also showed improved alkaline phosphate activity of bone marrow stem cells that were attached onto the surfaces of biomaterials [16].…”
Section: Introductionmentioning
confidence: 66%
“…[8][9][10] Electropho-retic deposition (EPD) of bioactive ceramics on metal substrates favors low sintering temperature and slow heating and cooling cycles that minimize interfacial stresses between metal and ceramic and enhance adhesion strength. [11][12][13] Coating bioactive silica-calcium phosphate nanocomposite (SCPC50) on Ti-6Al-4V orthopedic implant using EPD showed the adhesion strength at the interface between the metal substrate and the bioactive ceramic to be 47 6 4 MPa which exceeded the ASTM (F1147-05) requirement of 30 MPa. 11 Cell attachment to an implant is strongly governed by the amount, kind and conformation of proteins that adsorb onto the material's surface.…”
Section: Introductionmentioning
confidence: 99%